Vpliv pandemije covid-19 na pogodbe o paketnih potovanjih - Lutman, Karmen (Pravni letopis, 2020)
Tourism is one of the most affected sectors in the ongoing covid-19 crisis. The resorts remained empty for the most of the year and it is still difficult to predict how travel will look like next year. Due to the mass cancellations, tourism service providers have found themselves in an unenviable position, as legislation in this area is often more favourable to passengers. This article deals with the impact of the pandemic on package travel contracts regulated by the EU Directive no. 2015/2302. It focuses on the concept of "unavoidable and extraordinary circumstances" and their consequences for the contractual relationship. The legal analysis takes into consideration different stages of the ongoing pandemic and offers guidelines for resolving possible future disputes in this area. The final part of the article provides an insight into the first (foreign) court decisions dealing with the impact of the pandemic on package travel contracts.
Keywords: COVID-19; pandemije; pogodbeno pravo; potovanja; turizem